Bahasa Inggris - Dian Hasanah; Wiji Wiji; Sri Mulyani; Tuszie Widhiyanti (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze students' mental models on the concept of chemical bonds using a two-tier mental model diagnostic test. A test with the first tier asking the content and the second tier asking the reasons for the answers at the first tier. The test used has been developed and declared valid with a degree of reliability 0.751. This research is qualitative research with a case study design. Students' mental models are categorized into complete mental models, partial mental models, mental models with misconceptions, and mental models with inconsistencies. In the concept of chemical bonds found 17, 9, 15, and 59% of students with complete, partial, misconceptions, and inconsistencies in mental models respectively. Most students have misconceptions by stating that ionic bonds are formed through atomization and the formation of bonding electrons by reason of the sharing of electrons in ionic crystals. In addition, students understand that the process of forming covalent bonds in oxygen and fluorine occurs because of the attraction between atoms which is greater than the repulsion between bonded atoms. Among the inconsistent concepts found are students explaining the phenomenon of solubility, boiling point, and melting point based on the concept of the electron cloud.